Notes from the Packaging Laboratory: Hot Tack Measurements of Thin Sealant Films - Kenneth R. Berger; Matthew Knoelke; Bruce Welt (EDIS)
Sample preparation can greatly influence the results of laboratory testing of packaging sealant strength. Factors such as test strip width, edge uniformity, sealing die temperature and die load are recognizable variables to control. A design of experiments approach was used to explore the rank importance of these factors and any interactive effects that may occur. A generally well-behaved ethylene vinyl acetate (EVA) sealant on a high density polyethylene (HDPE) film was used for these tests. Experimental results indicate that sample width, die temperature and die pressure are the most influential factors. Unexpectedly, edge effects, namely a regular sine wave pattern and a generally random irregular edge had little influence on hot tack results. This document is ABE340, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published December 2002.